Development and Application of the Power Plant Real-Time Temperature and Stress Monitoring System - Piotr Duda (Science and Technology of Nuclear Installations)
The paper presents a method of temperature and stress estimation in pressure components of conventional or nuclear power plants. The proposed algorithm can be applied without the information concerning the thermal boundary condition on the component inner surfaces and it is fast enough to be applied in an online mode. The solution is possible thanks to “measured” temperature histories determined in easily accessible points located on the component outer surface. The presented model has been recently verified analytically, numerically, and experimentally. The proposed algorithm was used to calculate the transient temperature and stress distribution in the outlet header of a steam reheater and the results indicate that the component lower part is loaded the most, but allowable stresses are not exceeded. If the presented heating process was shortened, the calculated stresses would exceed the allowable values. Monitoring the boiler thermal and strength operating conditions makes it possible to identify dangerous loads of the power boiler pressure elements during transient-state operations. The presented method for controlling thermal and pressure-related stresses is suitable for nuclear power plants because it does not require drilling holes for sensors in the pressure element walls.